Correlation of Attitude and Subjective Norm to Behavior of Dental Care in Mothers with Pre-school Children - Idela, Cici; Renidayati; Sofian, Rizki; Rosmalia, Dewi (Journal Center of Excellent : Health Assistive Technology, 2025)
Early Childhood Caries (ECC) is susceptible to children under the age of six, which is pre-school age. The impact of ECC hampers the comfort of eating, speaking, and self-esteem, and it may last until the age of 71 months. Mother has a central role in preventing it from happening, yet few of them are aware of their children's dental health. This research aims to evaluate the correlation factors of attitude and subjective norm towards the behavior of mother in preserving their children’s dental health at an early age. This study was performed with a cross-sectional approach, on the basis of the Theory of Planned Behavior. There were 305 mothers in seven Kindergartens in Bukittinggi city involved as respondents. The analysis of correlation was conducted with multivariate analysis using Regression ANOVA. Questionnaires were used to obtain the data. The research resulted in the attitude obtaining an average of 50.32 and the Standard Deviation (SD) of 8.447. Meanwhile, the average of the subjective norm variable is 148.03, and the SD is 22.638. The attitude has a p-value of 0.025 (p<0.05) and subjective norm with 0.156 (p>0.05). In conclusion, attitude correlates with the mother’s behavior of preserving their children’s dental health. Meanwhile, the subjective norm doesn’t correlate with behavior.